Admission to Intensive Care for Palliative Care or Potential Organ Donation: Demographics, Circumstances, Outcomes, and Resource Use. Issue 10 (October 2017) - Melville, Andrew; Kolt, Gali; Anderson, David; Mitropoulos, Joanna; Pilcher, David
Abstract : Objectives: To describe the characteristics, circumstances, change over time, resource use, and outcomes of patients admitted to ICUs in Australia and New Zealand for the purposes of "palliative care of a dying patient" or "potential organ donation, " and compare with actively managed ICU patients. Design: A retrospective study of data from the Australian and New Zealand Intensive Care Society Adult Patient Database and a nested cohort analysis of a single center. Setting: One hundred seventy-seven ICUs in Australia and New Zealand and a nested analysis of one university-affiliated hospital ICU in Melbourne, VIC, Australia. Patients: Three thousand seven hundred "palliative care of a dying patient" and 1, 115 "potential organ donation" patients from 2007 to 2016. The nested cohort included 192 patients. Interventions: No interventions. Data extracted included patient demographics, diagnoses, length of stay, circumstances, and outcome of admission. Measurements and Main Results: ICU admissions for "palliative care of a dying patient" and "potential organ donation" increased from 179 in 2007 to 551 in 2016 and from 44 in 2007 to 174 in 2016 in each respective group, though only the "potential organ donation" cohort showed an increase in proportion of total ICU admissions. Lengths of stay in ICU were a mean of 33.8 hours (median, 17.5; interquartile range, 6.4–38.8) and 44.7 hours (26.6; 16.0–44.6), respectively, compared with 74.2 hours (41.5; 21.7–77.0) in actively managed patients. Hospital mortality was 86.6% and 95.9%, respectively. In the nested cohort of 192 patients, facilitating family discussions about goals of treatment and organ donation represented the most common reason for ICU admission. Conclusions: Patients admitted to ICU to manage end-of-life care represent a small proportion of overall ICU admissions, with an increasing proportion of "potential organ donation" admissions. They have shorter ICU lengths of stay than actively managed patients, suggesting resource use for these patients is not disproportionate. Abstract : Supplemental Digital Content is available in the text.